2006
DOI: 10.1109/jssc.2006.884188
|View full text |Cite
|
Sign up to set email alerts
|

More on the $1/{\rm f}^{2}$ Phase Noise Performance of CMOS Differential-Pair LC-Tank Oscillators

Abstract: Abstract-This paper presents a rigorous phase noise analysis in the 1 f 2 region for the differential CMOS LC-tank oscillator with both nMOS and pMOS switch pairs. A compact, closed-form phase noise equation is obtained, accounting for the noise contributions from both tank losses and transistors currents, which allows a robust comparison between LC oscillators built with either one or two switch pairs.The fabricated oscillator prototype is tunable between 2.15 and 2.35 GHz, and shows a phase noise of 144 dBc/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(64 citation statements)
references
References 13 publications
1
62
0
1
Order By: Relevance
“…6. The CMOS LC-VCO architecture with both NMOS and PMOS switch pairs is chosen for its lower power consumption than single-switch-pair oscillator [9]. For the LC-VCO, the resistor-switching for the current control is used, since it contributes less flicker noise than current mirror, and the chip area of the RC filter for the bias circuits is much more reduced.…”
Section: Other Building Blocks Of the Pllmentioning
confidence: 99%
“…6. The CMOS LC-VCO architecture with both NMOS and PMOS switch pairs is chosen for its lower power consumption than single-switch-pair oscillator [9]. For the LC-VCO, the resistor-switching for the current control is used, since it contributes less flicker noise than current mirror, and the chip area of the RC filter for the bias circuits is much more reduced.…”
Section: Other Building Blocks Of the Pllmentioning
confidence: 99%
“…Recent phase noise theory based on the impulse sensitivity function (ISF) theory of phase noise, together with a linear-time-variant circuit analysis [7], has shown that not only the small-signal transconductance must be considered. The VCO phase noise depends on the large-signal oscillation amplitude, and that is proportional to the bias current and the parallel tank resistance, which varies with frequency.…”
Section: Tank Loss Variationsmentioning
confidence: 99%
“…2, is formed by the classical differential CMOS LC oscillator. Having both pMOS and nMOS cross-coupled pairs does not significantly increase the noise of the oscillator while assuring a higher small signal negative resistance for a given bias current, making the startup of the oscillator more reliable, and achieving a doubled oscillation amplitude (which turns, ideally, into a 6 dB lower phase noise), compared to oscillators with a single switch pair using the same bias current [7]. Thus, this choice results in a more efficient current-reusing LMV cell, compared to the solutions in [5,[8][9][10].…”
Section: Self-oscillating Mixer and Lc Tankmentioning
confidence: 99%